Construction of an anti-hepatitis B virus preS1 antibody and usefulness of preS1 measurement for chronic hepatitis B patients: Anti-HBV PreS1 antibody. Issue 3 (March 2022) - Hatooka, Haruna; Shimomura, Yumi; Imamura, Michio; Teraoka, Yuji; Morio, Kei; Fujino, Hatsue; Ono, Atsushi; Nakahara, Takashi; Murakami, Eisuke; Yamauchi, Masami; Kawaoka, Tomokazu; Makokha, Grace Naswa; et al.
Highlights: The preS1 region plays an essential role in hepatitis B virus (HBV) infection. Construction of an antibody against preS1 and an ELISA system capable of measuring serum HBV preS1 levels. PreS1 levels are correlated with HBV markers such as HBsAg, HBcrAg and HBV DNA. PreS1 levels may serve as a novel tool to predict the need for antiviral therapy in HBeAg-negative HBV-infected patients. Summary: Objectives: The preS1 region plays an essential role in hepatitis B virus (HBV) infection. We construct an antibody that binds to preS1 and a measurement system for serum preS1 in chronic HBV-infected patients. Methods: Hybridoma clones that produce anti-preS1 antibodies were obtained by the iliac lymph node method. Epitope mapping was conducted, and an enzyme-linked immunosorbent assay (ELISA)-based method was developed. Using this ELISA system, serum preS1 levels were measured in 200 chronic HBV-infected patients. Results: Eight types of hybridomas were obtained, of which antibody 3–55 using amino acids 38–47 as the epitope showed high binding affinity to preS1. Serum preS1 levels measured by ELISA using 3–55 antibody were correlated with HBsAg, HBcrAg and HBV DNA levels. Among HBeAg-negative patients without antiviral therapeutic objective (HBV DNA <3.3 log IU/mL or alanine aminotransferase ≤30 U/L), preS1 was significantly higher in subjects who had progressed to the point of requiring antiviral therapy compared to subjects who had maintained their status for the preceding three years ( p <0.01). Conclusions: We constructed an antibody against preS1 and an ELISA system capable of measuring serum preS1 levels. PreS1 may serve as a novel tool to predict the need for antiviral therapy in HBeAg-negative HBV-infected patients.